Federal Republic of Yugoslavia : Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
The new government of the Federal Republic of Yugoslavia has formulated and started to implement an ambitious program of stabilization and reform with impressive speed and commitment. The program provides for macroeconomic policies designed to reduce inflation and support reconstruction coupled with bold reforms. The policy achievements so far have been impressive. Prudent policies alone cannot ensure progress toward sustainable growth and external viability. The program sets the basis for the country in achieving sustainable output growth and a viable external position.